2021
DOI: 10.3390/jof7121073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Native Entomopathogenic Fungi for the Control of Fall Armyworm (Spodoptera frugiperda) in Thailand: A Sustainable Way for Eco-Friendly Agriculture

Abstract: Fall armyworm, Spodoptera frugiperda, entered Thailand in late 2018 and has now spread in several regions, with devastating effects in maize and rice production, which are some of the most important cereals in the world. Since then, farmers have utilized the available chemical insecticides to try to control it, but their efforts have been futile. Instead, they have ended up using extraordinary dosages, hence threatening non-target species and other fauna and flora, as well as being costly. In this regard, rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…Interestingly, one isolate of B. bassiana caused significant larval mortality against FAW [ 44 , 60 ]. Another study reported that the presently studied isolates of B. bassiana significantly affected the larval growth of Dendrolimus pini [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, one isolate of B. bassiana caused significant larval mortality against FAW [ 44 , 60 ]. Another study reported that the presently studied isolates of B. bassiana significantly affected the larval growth of Dendrolimus pini [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a hemocytometer, the conidial suspensions were adjusted to concentrations of 1 × 10 6 , 10 7 and 10 8 conidia/mL [ 59 ]. A dose-dependent mortality effect has already been observed in previous laboratory studies by many authors, so as such three doses were selected in the present study in order to investigate if there is any different observation between this study with multiple doses and previous studies that used multiple doses to assess the virulence of B. bassiana isolates against FAW [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the baseline susceptibilities of different insecticides with control failure estimation for S. frugiperda were determined in Burkina Faso [ 15 ]. Entomopathogenic nematodes were used to control S. frugiperda in Thailand [ 16 ]. Insecticide ‘ampligo’ was used against S. frugiperda in the coastal Savannah agroecological zone of Ghana [ 17 ].…”
Section: Introductionmentioning
confidence: 99%